Transformation of Structure of Mythological Representations of Mountaineers during a Modernist Style Era - Lytvyn-Kindratiuk, Svitlana (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
In article approach to studying of structure of mythological representations of mountaineers during an era of modernization and globalization of a way of life is considered. The Psikhologo-historical foreshortening of the analysis allows to track communication of features of environment and difficulties of coordination to structure of primary and latest mythological representations of Huzuls.